Kajian Yuridis Perlindungan Hukum Terhadap Konsumen Akibat Perbedaan Harga Yang Pada Rak dan Kasir - Gustiawan K; Siti Muslimah Suciati; Aksah Kasim; Andi Heridah (Jurnal Litigasi Amsir, 2024)
This research is expected to be used as a reference in solving problems related to price differences on shelves and cashiers towards consumers and how Alfamart is responsible for the problems of price differences that exist on shelves and cash registers experienced by consumers. This research uses a normative-empirical research type with a statute approach and a social approach. The results of the study show that consumers can exercise their rights to hold Alfamart accountable due to differences in price tags on shelves and cash registers and Alfamart must be responsible by compensating for losses according to the price that must be paid by consumers and be more careful when replacing old price tags with the newest price tags on shelves so that consumers don't get confused.